INDEX OF VULNERABILITY OF WATER RESOURCES FOR IRRIGATION IN THE BASIN OF NARANJO RIVER, CUBA - García-Hidalgo, Yoandris (Revista Geográfica de América Central., 2017)
The vulnerability analysis of the Naranjo River Basin is a technical diagnostic study that provides basic and strategic information for the comprehensive management plan for water resources. For this study, six representative sections of the basin were considered. The vulnerability of the basin was determined through indicators of the hydrological regime and water quality based on FAO criteria for irrigation water. As a result, it was determined that the vulnerability index due to shortages has increased from moderate to high, and it has been attributed to the very low capacity for regulation and water retention and moderate use of the resource. The waters are not suitable for irrigation of agricultural crops, and they have slight to moderate restrictions. There is a danger of soil alkalization resulting from concentrations of bicarbonate in the water. The vulnerability could increase with the presence of some factors derived from climate change, due to the reduced supply and increased demand for water for agricultural activities in the area.